The Battle over the Soul of Law Professor Blogs - Howard J. Bashman (Washington University Law Review, 2006)
Unbeknownst to most of us outside the legal academy, there apparently is some disagreement over whether blogs that law professors operate should be regarded as legitimate scholarship and public service, or should be dismissed as a frivolous waste of time that detracts from the more traditional scholarly pursuits of writing massive law review articles and pontificating to the mainstream media on legal issues of public interest. As so often is the case, the answer to this conundrum is “It depends.” A law professor’s blog post or series of blog posts certainly can constitute scholarship or public service. But, merely because a blog post is written by a law professor does not guarantee that what results ought to be regarded as scholarship or public service, nor does every law professor blogger intend for every post, or even a majority of their posts, to constitute either scholarship or public service.
Keywords: Blogs; Law – Study & amp; teaching; Law school faculty; Legal literature; United States